Predatory Lending and Financial Vulnerability: A Bibliometric Review of Global Research Trends - Angel Jade V. Frialde; Evette Jillian R. Maiquez; Sheena S.P Ramos; Jennifer P. Solis (International Journal of Multidisciplinary: Applied Business and Education Research, 2026)
Lending institutions play an important role in helping people fulfill their financial requirements, handle unexpected situations, and support their personal needs or business operations. When done fairly, lending institutions provide access to funds that people may not currently have, helping them improve their financial security and opening new opportunities. However, lending becomes risky when it deviates from fair practices and results in predatory lending. The global problem of predatory lending continues to affect many borrowers as they become trapped in extended debt obligations due to deceptive loan conditions. This study examines how academic studies on predatory lending and financial vulnerability have evolved across different nations and academic disciplines. The Scopus database provided data for Bibliometrix (R) and VOSviewer to perform bibliometric analysis, which produced publication patterns, author rankings, and research subject areas covering all available studies from 1963 to 2025. Research on digital lending, poverty, and financial vulnerability in developing nations has emerged as a new area of study, where most existing studies focus on the United States housing market and subprime lending sector. The research indicates that scholars now link multiple fields of study to examine predatory lending as it requires knowledge from economics, law, and social sciences. The review highlights the increasing academic interest in responsible lending practices, which demand fair financial systems for vulnerable populations who use digital loans and low-income individuals. This study suggests helping improve the protection low-income borrowers and digital loan users in developing countries.